„MÓWIENIE JEST CZĘŚCIĄ PEWNEJ DZIAŁALNOŚCI, PEWNEGO SPOSOBU ŻYCIA”. O KOMPETENCJI LINGWISTYCZNEJ JAKO KOMPETENCJI GIER JĘZYKOWYCH - Szczepaniak, Jacek (Acta Neophilologica, 2013)
This paper presents one of the possibilities of a new view at the notion of linguistic competence based on the concept of language games by Ludwig Wittgenstein. In contrast to “mental” perception of language competence as universal grammar encoded in genome, it underlines the importance of performativity and mediality. The understanding of a message content refers necessarily to how we use words in specific language games and how we cope with various sign systems and media spaces. The concept of language games competence proposed by a German researcher Jan Georg Schneider is based on the latest, culture related research concerning mediality issues (including in particular transcriptivity as presented by Ludwig Jäger), performativity and theory of language.